A Narrative Review: Professional Ethics in Data Analysis for Medical Sciences - Hassan Doosti; Ali Ahmadi Amin (Mashhad University of Medical Sciences, 2024)
Background: Professional ethics has become an indispensable component of skills and various fields today. Disregarding ethical principles can have detrimental consequences for human society, especially when dealing with large and complex data in various branches of medical sciences. Adhering to professional ethical standards in data production and statistical analysis ensures the accuracy and validity of results derived from this data in the field of medical sciences. The primary objective of this article is to introduce and elucidate the principles of professional ethics in the analysis of medical data.Methods and Materials: In this narrative review study, we delve into an examination of articles and viewpoints presented in the realm of professional ethics. This examination encompasses a comprehensive analysis of the foundations of professional ethics in medical sciences and various approaches to this matter.Results and Conclusion: Incorporating ethical considerations in the domain of statistical activities and data analysis in medical sciences holds significant importance. These actions, including the evaluation of the value and credibility of each statistical action and decision, precise modeling, and efforts to find ethical solutions to ethical challenges in this field, can contribute to the improvement and advancement of medical sciences. Therefore, attention to the principles of professional ethics in data analysis in medical sciences stands out as an essential prerequisite for enhancing credibility and scientific assurance in this domain.